If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + y = 9 Solving 2c + y = 9 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1y' to each side of the equation. 2c + y + -1y = 9 + -1y Combine like terms: y + -1y = 0 2c + 0 = 9 + -1y 2c = 9 + -1y Divide each side by '2'. c = 4.5 + -0.5y Simplifying c = 4.5 + -0.5y
| 5abc*b=46 | | 5x-38=-2(1-7x) | | -7-24/6 | | 25=6 | | 4+hyt=8 | | b=4h | | (3v+8)(9-v)=0 | | 5+37+67= | | 33=3(10x-5)2(3x-10x) | | 1x=745 | | 5(9x-7)=190 | | 1x= | | (u+6)(u-4)=0 | | 5x+9=144 | | -32/8+3 | | -3(3p+4)-2(2-11p)=3(5+4p) | | (w+9)(w+5)=0 | | 236478+x=236490 | | -6+73-93-4= | | 4+w=7 | | -27=5u-7 | | -5(2-4)= | | 5-x=712 | | 5-x=71,2 | | 5z^2-23z-10=0 | | 64305628564*x=4621784512879451675438245216795461329546829 | | (3*85*15+12-11)+(62+18+48)= | | 5(-2+1)=-9(x+1) | | -6w+6=-3 | | x^3-x-1=0 | | -80X^2-44X+180=0 | | (29b-2)-7(4b+3)=-6 |